1987
DOI: 10.1002/j.1537-2197.1987.tb08772.x
|View full text |Cite
|
Sign up to set email alerts
|

Secretions From the Pistil of Lilium Longiflorum

Abstract: The pistil of Lilium longiflorum secretes two forms of exudate, one from the stigma surface and the other from the canal cavity. Electrophoretic studies of these exudates have revealed quantitative and qualitative differences in protein profiles. The exudatic components which are transferred to the cell wall by endoplasmic reticulum and Golgi vesicles, are stored within the cell wall of the secretive tissues and secreted from the cell walls directly. The cell wall structure of these secretive tissues differs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Secondly, the secretion is inhibited by self-pollination. Yamada (1965) and Miki-Hirosige et al (1987) showed histochemically that cross-pollination triggered the secretion of the canal exudate. In the present study, carbohydrate and protein contents of the canal exudate rather increased until 24 hr after self-pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the secretion is inhibited by self-pollination. Yamada (1965) and Miki-Hirosige et al (1987) showed histochemically that cross-pollination triggered the secretion of the canal exudate. In the present study, carbohydrate and protein contents of the canal exudate rather increased until 24 hr after self-pollination.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion into the canal can thus occur rapidly depending on the acceptivity of the pollen tubes (Miki-Hirosige et al 1987). In our observations, while a slight expansion and diffusion of the cell wall are seen, neither the cell wall nor the periplasm has a structural similarity to their counterparts in Lilium.…”
Section: Discussionmentioning
confidence: 60%
“…These grafting results lead us to assume that compatible pollen tubes stimulate the glands of the canal to actively secrete and thereby promote their unhindered growth to the ovary. This assumption is that compatible pollen tubes trigger the secretion by canal surface cells lining the stylar canal is supported by histochemical observations (Miki-Hirosige et al, 1987;Yamada, 1965).…”
Section: Growth Of Pollen Tubes In the Stylar Canal Flushed With Watermentioning
confidence: 75%